In-vivo MRI Reveals Changes to Intracerebral Vasculature Caliber in HIV Infection - De Alwis, Paba M.; Smith, Bryan R.; Wu, Tianxia; Artrip, Cristah; Steinbach, Sally; Morse, Caryn; Lau, Chuen-Yen; Rapoport, Stanley I.; Snow, Joseph; Tramont, Edmund; Reich, Daniel S.; Nair, Govind; et al. (Frontiers in Neurology, 2019)
Objective: To characterize cerebral arterial remodeling in HIV-infected (HIV+) individuals in-vivo, and to study its clinical and immunological associations. Methods: T2*-weighted magnetic resonance imagining sequences was used to determine cross-sectional area (vascular caliber) of the anterior (A1 segment) and middle (M1 segment) cerebral arteries in HIV- (control) and HIV+ subjects on antiretroviral therapy. Correlations of A1 caliber with clinical, demographic parameters, and immunological markers in cerebrospinal fluid (CSF) were determined using multivariable analyses. Results: A1 and M1 calibers from 22 HIV- control subjects (age: median 48.5 years, range 22-60 years, 55% male) and 61 HIV+ subjects (age: median 53 years, range 25-60 years, 67% male) were studied. ANCOVA, adjusting for ethnicity and sex (age was not correlated with M1 or A1 caliber in either group), revealed that HIV+ subjects had larger caliber in the A1 segment than HIV- subjects (4.95 ± 0.14 mm2, and 4.47 ± 0.21 mm2 respectively, p=0.048), but caliber of the M1 segment did not differ among the groups (7.21 ± 0.14 mm2 and 7.09 ± 0.23 mm2 respectively, p=0.65). In the HIV+ cohort, longer disease duration and higher current CD4 T-cell count were associated with reduced A1 caliber (r = -0.42 and -0.33 respectively, p<0.05). In addition, increase in CVD risk was associated with a decrease in A1 caliber in the HIV group (r = -0.35, p<0.05). Conclusions: This cross-sectional study reveals an increase in A1 caliber in the HIV+ cohort, compared to control subjects, which is especially prominent in early phase of the disease. This increase in caliber may be associated with acute pathological processes in HIV during the initial stages of infection resulting in loss of compliance or thinning of the arterial wall. At later stages, such changes may be confounded by arteriosclerotic changes that are common in later stages of HIV infection. This study suggests there is extensive vessel remodeling in various stages of infection. Long-term longitudinal follow-up of this cohort is planned to further verify this hypothesis and to better understand this MRI marker of intracranial vascular caliber.